Teaching grammar in public schools: a supervised internship experience. - SOUZA, Valdecy de (2023)
This Final Course Assignment had the general objective to show models of English language grammar used during the supervised internship in a second year high school. In order to reach this goal, three specific objectives were elaborated: to identify grammar teaching models in the classes taught; to recognize the differences and similarities of the models; and to describe my impressions about the influence of these models in my teaching practices. Thus, this qualitative research is characterized as a case study and ethnographic, focusing on the teaching of English grammar in the regular public context. The theoretical discussion was based on authors such as Celce-Murcia and Larsen-Freeman (2016), Larsen-Freeman-Anderson (2013), Thornbury (1999), among others. Thus, some questions helped me guide this work and direct the teaching of grammar, such as What models of English language grammar are used in my classes? What strategies are used during the classes? Why do I prefer to use the inductive model in my teaching practice? As main results, it was found that a great part of the lesson design and the application of the activities resemble deductive grammar.